MANAJEMEN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM (Studi Kasus di Institut Pertanian Bogor) - Furqon Syarief Hidayatulloh (Jurnal Pendidikan Islam, 2013)
This study aims at describing the implementation of management/management of Islamic Education (PAI) in Public Higher Education (PTU-Non-Religious). The research site chosen is the Bogor Institute of Agriculture (IPB). This study is a case study because it includes qualitative research. The data were collected through in-depth interviews, analysis and documentation of participatory observation. The results showed that the implementation of the PAI in IPB management generally includes: 1) procurement program of new teaching staff (determination of requirements, recruitment and selection, and appointment and assignment), 2) Management division of teaching schedule (Coordinator invites lecturers, lecturers are asked to select the days, hours and class in accordance with readiness, and selecting l teaching assisstant), 3) PAI Learning Management (Lecture, Assistance, and Studium General), and 4) follow-up program.